## Related questions with answers

Question

*Find the indicated derivative for each function.*

$h''(x)$ for $h(x)=2x^{-1}-3x^{-2}$

Solution

VerifiedAnswered 1 year ago

Answered 1 year ago

Step 1

1 of 3To find $h''(x)$, we find first the derivative of $h(x)$ then the derivative of $h'(x)$.

Using the Power Rule:

$f(x)=x^n\implies f'(x)=nx^{n-1}$

we solve for $h'(x)$:

$\begin{aligned}h(x)&=2x^{-1}-3x^{-2}\\ \implies h'(x)&=-1(2x^{-1-1})-(-2)(3x^{-2-1})\\ h'(x)&=-2x^{-2}+6x^{-3}&&\text{Simplify.} \end{aligned}$

## Create an account to view solutions

By signing up, you accept Quizlet's Terms of Service and Privacy Policy

## Create an account to view solutions

By signing up, you accept Quizlet's Terms of Service and Privacy Policy

## More related questions

1/4

1/7